ШАХСНИ ТАҲЛИЛ ҚИЛИШНИНГ КОНСТРУКТИВ МОДЕЛИ - Хужаев, Ф.А. (SCIENCE and SOCIETY, 2024)
The article describes the theoretical analysis of the constructive model of personality analysis. In particular, the scientific views and theories of foreign scientists regarding the constructive model of personality analysis were analyzed.
Keywords: constructivist; ethnic; cognitive; psychosocial; mythology; sociologist; identity; semantic; personal construction; constructive alternativeism; hypothesis